UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL EXPLICIT INSTRUCTION MATERI SIFAT-SIFAT BUNYI UNTUK SISWA KELAS IV SD NEGERI LOLEO - Wanti Hitto; Ridwan Jusuf; Wawan Suprianto Nadra (PEDAGOGIK, 2022)
This study aims to determine the application of the Explicit Instruction learning model to fourth gradestudents at SD Negeri Loleo and to determine the increase in student learning outcomes in grade IV SDNegeri Loleo. This research method is Classroom Action Research (CAR) conducted at SD NegeriLoleo in odd semesters. The subjects of this research were fourth grade students at SD Negeri Loleo,totaling 26 students. The results showed that in the learning outcomes of fourth grade students at SDNegeri Loleo in understanding the material properties of sound and its relation to the sense of hearing,the results of the first cycle test of students who did not complete were 17 students with a percentage of65.4% and there were 9 students who completed the percentage 34.6%. In the second cycle test, therewere 4 students who did not complete with a percentage of 15.4% and 22 students who passed with apercentage of 84.6%. Thus, it can be concluded that using the Explicit Instruction learning model canimprove the learning outcomes of fourth grade students at SD Negeri Loleo in understanding thematerial properties of sound and its relation to the senses of the listener